Teaching Vocabulary Using Food Package To The Fourth Year Student At SD Negeri Cemani 3 Sukoharjo In 2012/2013 Academic Year - Asari, Renawati Febri; , Drs. Djoko Srijono, M.Hum (2013)
Language is an important tool for the people to communicate each other. The function of language is very crucial to the continued life of the people. Without language, the people can't recognize each other. Languge can't be separated with vocabulary because these two elements are related each other. Vocabulary learning is an important part of any language learning process. Learning vocabulary helps the students understand English that is as a new language for them. It is the key for the people to communicate with each other. The writer focuses on teaching English vocabulary by using food packages to elementary students. The aim of this study is to increase vocabulary mastery through food package to the fourth year student of SD Negeri Cemani 3 Sukoharjo. The type of this study is descriptive research. The analysis is qualitative method where the data taken from observation, interview, and documentation. The object of this study is the implementation of teaching vocabulary using food package to increase the students' vocabulary mastery to the fourth year students of SD Negeri Cemani 3 Sukoharjo in 2012/2013 academic year. The result of the study shows that food package can increase the students' vocabulary mastery. Before the observation, the teacher's teaching technique was monotonous and the students easily get bored. The students tended to speak with other friends than to listen what the teacher said, the material can't be learned well, so the result of vocabulary mastery was poor. After the implementation of teaching vocabulary by using food package, the vocabulary mastery of the fourth year students of SD Negeri Cemani 3 Sukoharjo increases.